2020
DOI: 10.2147/cmar.s243918
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Hypoxia-Induced Aquaporin-3 Changes Hepatocellular Carcinoma Cell Sensitivity to Sorafenib by Activating the PI3K/Akt Signaling Pathway</p>

Abstract: Purpose: Hypoxia-induced changes are primarily activated in patients with hepatocellular carcinoma (HCC) and long-term sorafenib exposure, thereby reducing the sensitivity to the drug. Aquaporin-3 (AQP3), a member of the aquaporin family, is a hypoxia-induced substance that affects the chemosensitivity of non-hepatocellular tumors. However, its expression and role in the sensitivity of hypoxic HCC cells to sorafenib-induced apoptosis remain unclear. The purpose of this study was to detect changes in AQP3 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Sorafenib and UO126 (Sigma-Aldrich, St. Louis, Missouri, USA) were purchased and dissolved in 100% DMSO to prepare a 10mM stock solution, which was then diluted with DMEM to the desired concentration, with a nal concentration of 0.1% DMSO, recommended for in vitro studies. Unless otherwise stated, all antibodies were obtained from Life Span BioSciences (LSBIO, Seattle, Washington, USA) 32 . The enhanced chemiluminescence detection kit was purchased from Amersham Pharmacia Biotech-UK.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sorafenib and UO126 (Sigma-Aldrich, St. Louis, Missouri, USA) were purchased and dissolved in 100% DMSO to prepare a 10mM stock solution, which was then diluted with DMEM to the desired concentration, with a nal concentration of 0.1% DMSO, recommended for in vitro studies. Unless otherwise stated, all antibodies were obtained from Life Span BioSciences (LSBIO, Seattle, Washington, USA) 32 . The enhanced chemiluminescence detection kit was purchased from Amersham Pharmacia Biotech-UK.…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentration was determined via the bicinchoninic acid protein assay as per the Bio-Protocol (bioprotocol, Philadelphia, Pennsylvania, USA). An equivalent of 30μg of the protein extract was resolved via sodium dodecyl sulfate polyacrylamide gel electrophoresis and electro transferred (wet) to polyvinylidene di uoride membranes (EMD Millipore Corporation, Billerica, Massachusetts, USA) 32 . The membranes were initially blocked with 5% BSA in TBST (137mM NaCl, 20mM Tris HCl [pH 7.6], and 0.1% [v/v] Tween 20) for 1 h, followed by incubation overnight at 4°C with primary antibodies (1:1000) against AQP3, Erk, p-Erk, Akt, p-Akt, p53, p-p53, p21, cyclin-dependent kinase 2 (CDK2), cyclin-dependent kinase 4 (CDK4), and GAPDH/beta-tubulin (as loading controls).…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Yeh et al showed that galectin-1 is elevated in sorafenib-resistant HCC cells, both in vitro and in vivo, promoting tumor metastasis and increasing tumor invasion, suggesting that galectin-1 plays a role in downstream regulation of the AKT/mTOR/HIF-1 signaling pathway (113). Hypoxia induces overexpression of AQP3 in hypoxic HCC cells, thereby altering sensitivity of these cells to sorafenib by activating the PI3K/Akt signaling pathway (114).…”
Section: Hypoxic and Sorafenib-resistance In Hccmentioning
confidence: 99%